Creating the golden triangle of evidence‐informed education technology with EDUCATE. (26th December 2018) - Cukurova, Mutlu; Luckin, Rosemary; Clark‐Wilson, Alison
Abstract: EDUCATE is a London‐based programme that supports the development of research‐informed educational technology (EdTech), allowing entrepreneurs and start‐ups to create their products and services, and simultaneously grow their companies in a more evidence‐informed manner. The programme partners businesses with researchers who mentor, guide and support this research journey, a key aspect of which is the evaluation of the company's EdTech product or service. However, conducting impact evaluations of technology in education is challenging, particularly for early stage technologies, as rapid cycles of innovation and change are part of their essence. Here, we present the pragmatic approach to evidence‐informed education technology design and impact evaluation, as developed and adopted by the EDUCATE programme. The research process is shaped by the core principles of evidence‐informed decision making detailed in the paper. The contributions of the paper are threefold. First, it defines and details an academia‐industry‐education collaboration model centred on a research training programme. Second, it presents emerging impact results of the programme. Third, it provides clear reflections on the challenges encountered during the implementation of the model in the EdTech ecosystem of London, which should be addressed if we are to move towards evidence‐informed EdTech globally.